2010
DOI: 10.1186/gb-2010-11-12-r123
|View full text |Cite
|
Sign up to set email alerts
|

Predictive network modeling of the high-resolution dynamic plant transcriptome in response to nitrate

Abstract: BackgroundNitrate, acting as both a nitrogen source and a signaling molecule, controls many aspects of plant development. However, gene networks involved in plant adaptation to fluctuating nitrate environments have not yet been identified.ResultsHere we use time-series transcriptome data to decipher gene relationships and consequently to build core regulatory networks involved in Arabidopsis root adaptation to nitrate provision. The experimental approach has been to monitor genome-wide responses to nitrate at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
283
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(295 citation statements)
references
References 50 publications
(99 reference statements)
11
283
0
1
Order By: Relevance
“…Our data indicate that the nuclear export of NLP7 slows down within minutes after the addition of nitrate, allowing a rapid NLP7-dependent regulation of gene expression. Consistent with our data, Krouk et al 9 showed that gene expression is regulated by nitrate as rapidly as 2 min after supply. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data indicate that the nuclear export of NLP7 slows down within minutes after the addition of nitrate, allowing a rapid NLP7-dependent regulation of gene expression. Consistent with our data, Krouk et al 9 showed that gene expression is regulated by nitrate as rapidly as 2 min after supply. …”
Section: Discussionsupporting
confidence: 93%
“…S9). The OPP pathway is a critical step providing reductants for nitrate assimilation and has been shown to have a very early response to nitrate resupply 9 . Accordingly, the list of NLP7-dependent nitrate-inducible genes includes nitrate transporter NRT2.1, nitrate reductase NIA1, nitrite reductase, glutamine synthetase 2, uroporphyrinogen III methyltransferase 1, ferredoxin 3 and transketolase (At3g60750) ( We confirmed the modified nitrate-responsive expression pattern of these genes by quantitative reverse transcription-PCR (Supplementary Figs S10 and S11).…”
Section: Resultsmentioning
confidence: 99%
“…We compared the list of misregulated genes in the rsa1-1 mutant to a list of 3,186 genes regulated by the synthetic auxin naphthalene-1-acetic acid in the root (26). We found significant overrepresentations of the intersections of auxin-regulated genes with genes misregulated in the rsa1-1 mutant for both of our datasets (P < 0.001), compared with random generated gene lists of the same size (27,28), further suggesting a rsa1-1 role in auxin homeostasis. To further test whether expression of RSA1 mRNA is causative to changes in root allometry, we tested whether natural variation in RSA1 activity is correlated with changes in PC2 COL .…”
Section: Identification Of Candidate Genes Underlying Natural Variatimentioning
confidence: 95%
“…At this point in time, nitrate application had affected the expression of 1,120 genes ($20 'unique hit' counts [DEseq] in treatment and/or controls, FDR , 0.01 and FC $ [2]). The reaction to nitrate occurred in what might be called a 'module-like' fashion, meaning that a number of genes in a dynamic and flexible gene network shifted the metabolism in a particular direction (Krouk et al, 2010a(Krouk et al, , 2010b.…”
Section: The Effect On Nodulinsmentioning
confidence: 99%
“…A transcriptome study revealed that 550 genes were differentially expressed in the roots of this plant within 20 min after nitrate application (Krouk et al, 2010a). Estimates based on summarizing microarray data from various studies have revealed that, depending on the overall experimental context, up to approximately one-tenth of the whole genome of Arabidopsis can be influenced by the presence of nitrate (Krouk et al, 2010b).…”
mentioning
confidence: 99%